Ultra-drying: A simple and cost-effective method for seed conservation - Radhamani, J; Singh, Neeta; Srinivasan, Kalyani; Tyagi, R K (Indian Farming, 2015)
The seed water content should be optimized for long-term conservation of germplasm. It can help in a situation wherever refrigeration facilities are not available. In tropical regions where temperatures range from 25-45Â°C, the optimum water content can be achieved by drying to 15% RH (ambient temperature) or at 20Â°C and 10% RH. However, the extent of improvement in longevity on ultra-desiccation appears to be species specific. From a practical point of view, ultra-drying should be potentially used as cost-effective technique for storage of seeds for national programmes to conserve their seed collections with high viability for increased durations. The technique can be further exploited in other agri-horticultural species for extending seed storability especially for farmers who can store their seeds well from one harvesting to the next growing season.